A high ionic mobility sulfide solid state electrolyte and method of making same
Patent Information
- Application Number
- CN202610580397.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-29
- Publication Date
- 2026-08-18
AI Technical Summary
[0006]本申请的主要目的在于提供一种高离子迁移率硫化物固态电解质及其制备方法,旨在解决现有固态电解质无法兼具低迁移活化能和高离子电导率的问题
本发明的高离子迁移率硫化物固态电解质,在硫化物固态电解质中引入Te元素,Te元素高极化率特性可以降低Li+迁移活化能;利用Te元素与S元素之间的高极化率差异,削弱固态电解质的晶格骨架刚性,实现强晶格软化;同时,通过结构侧Ge、S双位点协同掺杂生成锂空位,具体的,Ge位点以Sb5+、As5+等高价态阳离子取代Ge4+生成锂空位,S位点引入Cl-、Br-等卤素阴离子部分取代S2-同步生成锂空位,以此实现反Meyer-Neldel规则的调控效果。基于上述的Te诱导晶格软化-锂空位补偿协同作用,实现硫化物固态电解质室温、低温离子电导率双提升与锂离子迁移活化能降低的协同优化,进而获得高有效Li+浓度和宽温域适配性的硫化物固态电解质。
Smart Images

Figure CN122599515A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state batteries, and more particularly to a sulfide solid electrolyte with high ion mobility and its preparation method. Background Technology
[0002] Based on their crystal structures, sulfide electrolytes are mainly classified into LGPS type and argentite-germanium type. LGPS type is characterized by a tetragonal Li₂ crystal system. 10 GeP2S 12 As a typical example, its anionic sublattice adopts body-centered cubic stacking, forming a three-dimensional framework composed of [P / Ge]S4 tetrahedra, and its room temperature ionic conductivity is as high as 12 mS·cm. -1 The sulfide-germanium sulfide type has Ag8GeS6 as its structural prototype, and its lithium-based derivatives have Li7PS6 as their parent phase. To further improve the ion transport performance of sulfide solid electrolytes and overcome the technical bottlenecks of insufficient low-temperature ion mobility and high activation energy, researchers have developed various lattice control strategies, among which elemental doping-induced lattice softening is one of the most effective methods. This strategy introduces dopant elements with different polarizabilities from the matrix elements to reduce the lattice barrier that lithium ions must overcome during migration, thereby lowering the activation energy.
[0003] In the field of sulfide solid electrolyte research, the lattice softening effect can effectively suppress T, which is closely related to lithium-ion migration behavior. d Symmetric mode vibration. Where, T d This refers to the tetrahedral point group symmetry inherent in the tetrahedral framework of anions, typically represented by [PS4]. 3- The T2 vibrational mode of the tetrahedron. Lattice softening can significantly reduce the amplitude of this vibrational mode, thereby fundamentally reducing the activation energy of lithium-ion migration, and is the core regulatory means to optimize the ion transport performance of sulfide electrolytes.
[0004] Currently, the doping elements used in the industry for lattice softening and performance improvement of sulfide solid electrolytes are still concentrated in elements such as Se, Cl, Br, and I. These elements have limited differences in polarizability and ionic radius compared with the matrix element S, and can only achieve a weak lattice softening effect. As a result, the reduction in lithium-ion migration activation energy is close to the theoretical bottleneck, and the core problem of insufficient low-temperature ion mobility cannot be solved from the root.
[0005] Furthermore, existing lattice softening techniques are generally constrained by the enthalpy-entropy (Meyer-Neldel) compensation rule. While reducing the activation energy of lithium-ion migration through lattice softening, it often results in a decrease in the pre-exponential factor of ionic conductivity, making it difficult to achieve synergistic optimization of activation energy and ionic conductivity. This further limits the development of sulfide solid electrolytes such as Li. + Improved transmission performance. Summary of the Invention
[0006] The main objective of this application is to provide a sulfide solid electrolyte with high ion mobility and its preparation method, aiming to solve the problem that existing solid electrolytes cannot simultaneously possess low migration activation energy and high ion conductivity.
[0007] To achieve the above objectives, this application provides a high-ion-mobility sulfide solid electrolyte, characterized in that the chemical formula of the solid electrolyte is Li. θ Ge α P β Q ε S γ Te δ X 12-δ-γ Wherein, Q is Sb, As, Nb, or V, and X is Cl, Br, or I; θ+4α+5(β+ε)-(γ+δ)-12=0, 9.5≤θ<10, 1<α≤2, 1<β≤2, 2.7≤α+β+ε≤3.2, 10.5<γ<12, 0<δ≤0.6; the ionic conductivity of the solid electrolyte at 25-30℃ is 12.48 mS·cm. -1 The ionic conductivity at -50℃ is greater than or equal to 1 mS·cm. -1 .
[0008] To achieve the above objectives, this application also provides a method for preparing a high-ion-mobility sulfide solid electrolyte, comprising: grinding and mixing Li₂S powder, GeS₂ powder, S powder, P powder, Te powder, LiX powder, and Q₂S₅ powder according to the chemical formula of the solid electrolyte to obtain a mixed precursor; ball milling the mixed precursor to obtain a mixed precursor powder; cold pressing the mixed precursor powder to obtain a mixed precursor sheet; transferring the mixed precursor sheet into a quartz tube, introducing an inert gas into the quartz glass tube, and sealing the quartz tube by necking and melting; heating the quartz tube to 250°C to 350°C at a rate of 2 to 10°C / min, holding at that temperature for 5 to 15 hours, and then cooling it in a quenching medium for 10 to 30 minutes to obtain a solid electrolyte.
[0009] Optionally, the mixed precursor is ball-milled to obtain mixed precursor powder, comprising: placing the mixed precursor in a ball mill jar, adding grinding balls, and placing the ball mill jar in a ball mill, and ball-milling at a speed of 600~1200 rpm for 5~30 h to obtain initial mixed precursor powder; wherein, the ball-to-material ratio in the ball mill jar is 2~1:1, and the particle size of the grinding balls is 2~8 mm; and grinding the initial mixed precursor powder in a mortar for 15~30 min to obtain mixed precursor powder.
[0010] Optionally, during the cold pressing process, the pressure is 100~400MPa and the holding time is 2~10min.
[0011] Optionally, after cooling in a quenching medium for 10-30 minutes, the method further includes grinding the product inside the quartz tube in a mortar for 15-30 minutes.
[0012] Optionally, the inert gas is one or a combination of argon, helium, and nitrogen.
[0013] Optionally, the quenching medium is liquid nitrogen, an ice-water mixture, or a dry ice-ethanol mixture.
[0014] Compared with the prior art, the beneficial effects of this application are as follows: The high ion mobility sulfide solid electrolyte of the present invention introduces the Te element into the sulfide solid electrolyte. The high polarizability of the Te element can reduce the Li + Migration activation energy; utilizing the high polarizability difference between Te and S elements to weaken the lattice framework rigidity of the solid electrolyte, achieving strong lattice softening; simultaneously, lithium vacancies are generated through synergistic doping of Ge and S sites on the structural side, specifically, Ge sites are induced to form Sb sites. 5+ As 5+ High-valence cation-substituted Ge 4+ Lithium vacancies are generated, and Cl is introduced at the S site. - ,Br - Halogen anions partially substituted S 2- Simultaneous generation of lithium vacancies achieves the anti-Meyer-Neldel rule regulation effect. Based on the aforementioned synergistic effect of Te-induced lattice softening and lithium vacancy compensation, a synergistic optimization is achieved, resulting in both improved room-temperature and low-temperature ionic conductivity of the sulfide solid electrolyte and a reduced lithium-ion migration activation energy, thereby obtaining highly efficient Li... + Sulfide solid electrolytes with high concentration and wide temperature range adaptability.
[0015] The method for preparing a high-ion-mobility sulfide solid electrolyte of the present invention is based on structural improvements. It employs a high-energy ball milling-low-temperature annealing-quenching process to treat the system, introducing a disordered lattice state while retaining a high concentration of lithium vacancies. This synergistically enhances the effective Li+ concentration, broadens ion migration channels, and compensates for insufficient migration driving force caused by lattice softening, achieving a dual improvement in ionic conductivity at both room temperature and low temperature. The room-temperature ionic conductivity can reach 12.48 mS·cm. -1 The ionic conductivity at -50℃ can be ≥1 mS·cm -1The preparation process is simple and controllable, requiring no special customized equipment. Compared with the high-temperature sintering process of traditional sulfide electrolytes, it can significantly reduce the threshold for large-scale production, providing key materials and technical support for the stable range of electric vehicles in special scenarios such as low temperature and high altitude, as well as the practical application and industrialization of all-solid-state batteries for wide-temperature-range energy storage. Attached Figure Description
[0016] Figure 1 Phonon spectra for comparative examples and embodiments: (a) comparative example, (b) embodiment; Figure 2 Li ion migration barrier diagrams for comparative and example cases; Figure 3 The example shows the charge-discharge long-cycle performance curves at room temperature and a 0.5 C rate for 1000 cycles. Figure 4 The examples and comparative examples are shown in the charge-discharge long-cycle performance curves at a low temperature (-10°C) and a 2C rate for 1000 cycles. Figure 5 The Arrhenius fitting curves of ionic conductivity for the examples and comparative examples are shown.
[0017] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0019] The first embodiment of the present invention provides a high-ion-mobility sulfide solid electrolyte, wherein the chemical formula of the solid electrolyte is Li. θ Ge α P β Q ε S γ Te δ X 12-δ-γ Wherein, Q is Sb, As, Nb, or V, and X is Cl, Br, or I; θ+4α+5(β+ε)-(γ+δ)-12=0, 9.5≤θ<10, 1<α≤2, 1<β≤2, 2.7≤α+β+ε≤3.2, 10.5<γ<12, 0<δ≤0.6; the ionic conductivity of the solid electrolyte at 25-30℃ is 12.48 mS·cm. -1The ionic conductivity at -50℃ is greater than or equal to 1 mS·cm. -1 .
[0020] In this embodiment, Te element is introduced into the sulfide solid electrolyte. The high polarizability difference between Te and S elements weakens the rigidity of the solid electrolyte's lattice framework, achieving strong lattice softening. Simultaneously, lithium vacancies are generated through synergistic doping of Ge and S sites on the structural side. Specifically, the Ge sites are doped with Sb... 5+ As 5+ High-valence cation-substituted Ge 4+ Lithium vacancies are generated, and Cl is introduced at the S site. - ,Br - Halogen anions partially substituted S 2- Simultaneous generation of lithium vacancies achieves the anti-Meyer-Neldel rule regulation effect. Based on the aforementioned synergistic effect of Te-induced lattice softening and lithium vacancy compensation, a synergistic optimization is achieved, resulting in both improved room-temperature and low-temperature ionic conductivity of the sulfide solid electrolyte and a reduced lithium-ion migration activation energy, thereby obtaining highly efficient Li... + Sulfide solid electrolytes with high concentration and wide temperature range adaptability.
[0021] The second embodiment of the present invention provides a method for preparing a sulfide solid electrolyte with high ion mobility, specifically including the following steps: Step S1: According to the proportion of the chemical formula of the solid electrolyte, Li2S powder, GeS2 powder, S powder, P powder, Te powder, LiX powder and Q2S5 powder are ground and mixed to obtain a mixed precursor. Wherein, LiX is LiCl, LiBr, or LiI; Q2S5 is Sb2S5, As2S5, Nb2S5, or V2S5. The total mass of Li2S powder, GeS2 powder, S powder, P powder, Te powder, LiX powder, and Q2S5 powder is 400~800mg.
[0022] Specifically, before grinding and mixing, the raw materials need to be vacuum dried at 50~80 ℃ for 8~14 h. The dried raw materials are then added to an agate mortar and ground and mixed for 15~30 min. During the grinding process, the materials are continuously stirred to ensure that there is no obvious agglomeration.
[0023] Step S2: The mixture precursor is ball-milled to obtain mixture precursor powder; Specifically, the mixed precursor is placed in a ball mill jar, grinding beads are added, and the ball mill jar is placed in a ball mill and ball milled at a speed of 600~1200 rpm for 5~30 hours to obtain the initial mixed precursor powder. The ball mill adopts a pulse frequency conversion mode, changing direction every 5~15 minutes to avoid material accumulation. The ball-to-material ratio in the ball mill jar is 2~1:1, and the particle size of the grinding beads is 2~8 mm. Single particle size can be selected, or a mixture of 2~4 mm and 5~8 mm grinding beads can be used. The initial mixed precursor powder is then placed in a mortar and ground for 15~30 minutes to obtain the mixed precursor powder.
[0024] Step S3: The mixed precursor powder is cold-pressed to obtain a mixed precursor sheet; The mixed precursor powder is cold-pressed in batches. Specifically, 40-80 mg of mixed precursor powder is taken each time, poured into a polyetheretherketone or alumina mold with a diameter of 10 mm, and placed on a tablet press to apply a pressure of 100-400 MPa for unidirectional pressing. The holding time is 2-10 min to obtain mixed precursor tablets.
[0025] Step S4: Transfer the mixed precursor sheet into a quartz tube, introduce an inert gas into the quartz glass tube, and seal the quartz tube by necking and melting; the inert gas is one or more combinations of argon, helium, and nitrogen.
[0026] Specifically, the mixed precursor sheets are transferred into a quartz tube, and the quartz tube is connected to a vacuum pump for continuous evacuation until the vacuum level inside the tube reaches 1×10⁻⁶. -4 Pa~3×10 -4 Pa; Inert gas is introduced into the quartz tube until the pressure inside the tube is close to atmospheric pressure to avoid electrolyte oxidation; The quartz tube is fired using a flame gun at 3000℃~3500℃ to melt and seal the necking of the quartz tube.
[0027] Step S5: The quartz tube is heated to 250℃~350℃ at a rate of 2~10℃ / min for annealing, and held at this temperature for 5~15 hours to complete the solid-phase reaction. The product of the solid-phase reaction is then immediately placed in a quenching medium at a cooling rate >100℃ / min for 10~30 minutes. The cooled product is then ground in a mortar for 15~30 minutes to obtain a homogeneous solid electrolyte. The quenching medium is liquid nitrogen, an ice-water mixture, or a dry ice-ethanol mixture.
[0028] In this embodiment, the high polarizability of Te is utilized to reduce the Li +The activation energy of lithium migration is optimized. On the structural side, lithium vacancies are generated through Ge and S dual-site heterovalent doping. On the process side, a high-energy ball milling-low-temperature annealing-quenching process strategy is used to treat the system, introducing a lattice disordered state while retaining a high concentration of lithium vacancies, thereby synergistically improving the effective lithium concentration. + By increasing the concentration and widening the ion migration channels, the insufficient migration driving force caused by lattice softening is compensated, thus achieving a dual improvement in ionic conductivity at both room temperature and low temperature.
[0029] Example 1 Preparation of Li 9.525 Ge 1.275 Sb 0.225 P 1.55 S 11.2 Cl 0.5 Te 0.3 LGPS type sulfide solid electrolyte Step S10: Mix Li2S powder, GeS2 powder, P powder, S powder, Te powder, Sb2S5 powder and LiCl powder according to stoichiometric ratio, with a total raw material weight of 500 mg; place all raw materials in a glove box and vacuum dry at 75 ℃ for 10 h, with water content <0.1 ppm and oxygen content <0.1 ppm in the glove box; place the dried raw materials in an agate mortar and grind and mix for 25 min, continuously stirring during the grinding process to obtain a mixed precursor; Step S20: Place the mixed precursor in a ball mill jar, add zirconia grinding balls, and place the ball mill jar in a ball mill. Perform high-energy ball milling at 800 rpm for 20 hours to obtain initial mixed precursor powder. The ball mill uses a pulse-type frequency conversion mode, changing direction every 10 minutes of grinding. The ball-to-material ratio in the ball mill jar is 1:1, and the grinding balls have a mixed particle size of 2 mm, 4 mm, and 6 mm. Grind the initial mixed precursor powder in a mortar for 15 minutes to obtain the mixed precursor powder.
[0030] Step S30: Take 50 mg of mixed precursor powder each time, pour it into a polyether ether ketone mold with a diameter of 10 mm, place it on a tablet press and apply a pressure of 200 MPa for unidirectional compression, and hold the pressure for 2 min to obtain mixed precursor tablets; repeat multiple times until all the mixed precursor powder is compressed into mixed precursor tablets.
[0031] Step S40: Transfer the mixed precursor sheet into a quartz tube, connect the quartz tube to a vacuum pump and continuously evacuate until the vacuum level inside the tube reaches 2×10⁻⁶. -4 Pa; Argon gas is introduced into the quartz tube until the gas pressure inside the tube is close to atmospheric pressure; The quartz tube is heated with a flame gun at 3000℃ to melt and seal the necking of the quartz tube.
[0032] In step S50, the sealed quartz tube is placed in a muffle furnace for heat treatment, and the temperature is increased to 280°C at a rate of 4°C / min for annealing. The temperature is held for 12 hours to complete the solid-phase reaction. The product of the solid-phase reaction is immediately placed in liquid nitrogen and cooled at a rate >100°C / min for 15 minutes. After cooling, the quartz tube is removed, transferred to a glove box for crushing, and the solid electrolyte sample inside is taken out and ground in a mortar for 20 minutes to obtain a uniform solid electrolyte.
[0033] Example 2 Preparation of Li 9.66 Ge 1.16 Nb 0.29 P 1.55 S 11.1 Br 0.5 Te 0.4 LGPS type sulfide solid electrolyte Step S10: Mix Li2S powder, GeS2 powder, P powder, S powder, Te powder, Sb2S5 powder, and LiBr powder according to stoichiometric ratio, with a total raw material weight of 500 mg; place all raw materials in a glove box and vacuum dry at 70 ℃ for 12 h, with water content <0.1 ppm and oxygen content <0.1 ppm in the glove box; place the dried raw materials in an agate mortar and grind and mix for 30 min, continuously stirring during the grinding process to obtain a mixed precursor; Step S20: Place the mixed precursor in a ball mill jar, add zirconia grinding balls, and place the ball mill jar in a ball mill. Perform high-energy ball milling at 900 rpm for 25 hours to obtain initial mixed precursor powder. The ball mill uses a pulse-type frequency conversion mode, changing direction every 10 minutes of grinding. The ball-to-material ratio in the ball mill jar is 1.5:1, and the grinding balls have a mixed particle size of 2 mm, 4 mm, and 6 mm. Grind the initial mixed precursor powder in a mortar for 20 minutes to obtain the mixed precursor powder.
[0034] Step S30: Take 50 mg of mixed precursor powder each time, pour it into a polyether ether ketone mold with a diameter of 10 mm, place it on a tablet press and apply a pressure of 200 MPa for unidirectional compression, and hold the pressure for 4 min to obtain mixed precursor tablets; repeat multiple times until all the mixed precursor powder is compressed into mixed precursor tablets.
[0035] Step S40: Transfer the mixed precursor sheet into a quartz tube, connect the quartz tube to a vacuum pump and continuously evacuate until the vacuum level inside the tube reaches 2.5 × 10⁻⁶. -4 Pa; Argon gas is introduced into the quartz tube until the gas pressure inside the tube is close to atmospheric pressure; The quartz tube is heated with a flame gun at 3000℃ to melt and seal the necking of the quartz tube.
[0036] In step S50, the sealed quartz tube is placed in a muffle furnace for heat treatment, and the temperature is increased to 320°C at a rate of 5°C / min for annealing. The temperature is held for 10 hours to complete the solid-phase reaction. The product of the solid-phase reaction is then immediately placed in liquid nitrogen and cooled at a rate >100°C / min for 20 minutes. After cooling, the quartz tube is removed, transferred to a glove box for crushing, and the solid electrolyte sample inside is taken out and ground in a mortar for 25 minutes to obtain a uniform solid electrolyte.
[0037] Example 3 Preparation of Li 9.73 Ge 1.23 As 0.27 P 1.5 S 11.2 Cl 0.5 Te 0.3 LGPS type sulfide solid electrolyte Step S10: Li2S powder, GeS2 powder, P powder, S powder, Te powder, As2S5 powder, and LiCl powder are mixed according to stoichiometric ratio, with a total raw material weight of 500 mg; all raw materials are placed in a glove box and vacuum dried at 75 °C for 14 h, with a water content of <0.1 ppm and an oxygen content of <0.1 ppm in the glove box; the dried raw materials are placed in an agate mortar and ground and mixed for 28 min, with continuous stirring during the grinding process, to obtain a mixed precursor; Step S20: Place the mixed precursor in a ball mill jar, add zirconia grinding balls, and place the ball mill jar in a ball mill. Perform high-energy ball milling at 1000 rpm for 30 hours to obtain initial mixed precursor powder. The ball mill uses a pulse-type frequency conversion mode, changing direction every 15 minutes of grinding. The ball-to-material ratio in the ball mill jar is 2:1, and the grinding balls have a mixed particle size of 2 mm, 4 mm, and 6 mm. Grind the initial mixed precursor powder in a mortar for 30 minutes to obtain the mixed precursor powder.
[0038] Step S30: Take 50 mg of mixed precursor powder each time, pour it into a polyether ether ketone mold with a diameter of 10 mm, place it on a tablet press and apply a pressure of 300 MPa for unidirectional compression, and hold the pressure for 4 min to obtain mixed precursor tablets; repeat multiple times until all the mixed precursor powder is compressed into mixed precursor tablets.
[0039] Step S40: Transfer the mixed precursor sheet into a quartz tube, connect the quartz tube to a vacuum pump and continuously evacuate until the vacuum level inside the tube reaches 3×10⁻⁶. -4 Pa; Argon gas is introduced into the quartz tube until the gas pressure inside the tube is close to atmospheric pressure; The quartz tube is heated with a flame gun at 3000℃ to melt and seal the necking of the quartz tube.
[0040] In step S50, the sealed quartz tube is placed in a muffle furnace for heat treatment, and the temperature is increased to 350°C at a rate of 50°C / min for annealing. The temperature is held for 10 hours to complete the solid-phase reaction. The product of the solid-phase reaction is immediately placed in liquid nitrogen and cooled at a rate >100°C / min for 25 minutes. After cooling, the quartz tube is removed, transferred to a glove box for crushing, and the solid electrolyte sample inside is taken out and ground in a mortar for 30 minutes to obtain a uniform solid electrolyte.
[0041] Comparative Example 1 The difference from Example 1 is that the chemical formula of the fixed electrolyte is Li. 10 GeP2S 12 No Te, Q, or X dopants were added.
[0042] Comparative Example 2 The difference from Example 1 is that the ball milling process in step S20 was not performed, and the product was not placed in a quenching medium for quenching after the solid-state reaction was completed in step S50.
[0043] The ionic conductivity of the LGPS-type solid electrolytes in Examples 1-3 and the comparative examples is shown in Table 1: Table 1 Ionic conductivity of LGPS type solid electrolyte
[0044] As shown in Table 1, within the test temperature range of 223 K to 358 K, the ionic conductivity of Examples 1 to 3 is higher than that of Comparative Examples 1 to 2, which is particularly significant at room temperature (298 K): the conductivity of the Examples is significantly better than that of the Comparative Examples. This fully demonstrates that the synergistic modification strategy of Te-induced lattice softening and lithium vacancy compensation can effectively improve the ionic conductivity of high-entropy LGPS type sulfide electrolytes at room temperature.
[0045] Figure 1 (a) Li is the Li of Comparative Example 1 10 GeP2S 12 , Figure 1(b) is the 2×2 supercell phonon density of states (DOS) spectrum of Example 1. The lattice vibration characteristics of the two are significantly different: the main peak of Comparative Example 1 is located at 7.2 THz, the phonon band center is at 7.80 THz, and the vibration energy is concentrated in the mid-to-high frequency range; the main peak of Example 1 is significantly redshifted to 1.7 THz, the band center drops to 6.08 THz, and the low-frequency (<10 THz) phonon density of states is significantly enhanced. This indicates that the lattice vibration of Example 1 is significantly softened, and the anharmonicity and phonon scattering effect are greatly improved. Combined with the structural illustration, it can be seen that this modification strategy effectively regulates the lattice dynamics behavior and provides core theoretical support for optimizing the ion transport performance of sulfide solid electrolytes.
[0046] Figure 2 Li was shown in Comparative Example 1 10 GeP2S 12 Compared with the free energy barrier for lithium-ion migration in Example 1, the results show that the activation energy (E) for lithium-ion migration in Example Sample is significantly lower. a2 =0.25 eV) is significantly lower than the activation energy of the comparative example (E a1 =0.62eV), the barrier reduction in the example exceeded 59%, proving that the modification strategy effectively reduced the barrier to lithium-ion migration and optimized the kinetics of lithium-ion transport.
[0047] Figure 3 The full cell assembled in Example 1 exhibits long-term cycling performance curves after 1000 cycles at 25°C room temperature and 0.5 C rate. The battery demonstrates excellent cycle stability throughout the 1000 cycles, maintaining a coulombic efficiency consistently close to 100%, and an initial specific capacity of approximately 190 mAh·g. -1 The excellent capacity retention after cycling with no significant decay demonstrates that the sulfide solid electrolyte of this embodiment can achieve stable lithium-ion transport and interface compatibility in a high-load cathode system, and has excellent practical application potential.
[0048] Figure 4 The figure shows the example Sample and the comparative example Li. 10 GeP2S 12 A comparison of the low-temperature, high-rate, long-cycle performance of the assembled full cell under -10℃ and 2C rate conditions for 1000 cycles was conducted, with a positive electrode loading of 12.73 mg·cm³. -2 Comparative example Li 10 GeP2S 12 The battery failed after approximately 300 cycles, while the sample battery in the example still maintained a capacity retention of 83.36% after 1000 cycles, with a coulombic efficiency consistently remaining near 100%. This fully demonstrates that the modified electrolyte exhibits significantly superior performance compared to traditional Li-ion batteries under low-temperature, high-rate operating conditions.10 GeP2S 12 Its cycle stability and ion transport capability can meet the application requirements of solid-state batteries in extreme environments.
[0049] Figure 5 The figures show the Arrhenius fitting curves of the ionic conductivity of Samples 1, 2, and 3 (Samples 1, 2, and 3) and Comparative Examples 1 and 2. As can be seen from the figures, the fitting curve of Comparative Example 1, which was not modified with Te, Q, or X doping, shows a significant linear abrupt change at approximately 263 K, indicating that Li... + The conduction mechanism degenerates from three-dimensional (3D) conduction to one-dimensional (1D) conduction; however, the samples of Examples 1-3, which were synergistically regulated by Te-induced lattice softening and lithium vacancy compensation, maintained excellent linearity across the entire test temperature range of 220 K to 380 K, proving that this strategy successfully broadened and stabilized Li + The three-dimensional conduction pathway was observed. Furthermore, the three-dimensional conduction activation energies of the sample examples were all below 0.20 eV, significantly better than the 0.262 eV of Comparative Example 1, further validating the modified Li... + The migration barrier was effectively reduced. At a low temperature of 223 K, the ionic conductivity of the example samples remained at approximately 1 mS·cm. -1 Meanwhile, the ionic conductivity of Comparative Example 1 has decreased to 0.05 mS·cm. -1 The following demonstrates that this synergistic regulation strategy can significantly improve the low-temperature ionic conductivity of sulfide solid electrolytes. Furthermore, the conductivity level of Comparative Example 2 across the entire temperature range is lower than that of all other example samples, further confirming the crucial role of ball milling and quenching processes in optimizing ion transport performance and constructing stable three-dimensional conduction pathways.
[0050] The above are merely preferred embodiments of this application and do not limit the patent scope of this application. Any equivalent structural or procedural transformations made using the content of this application's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of this application.
Claims
1. A sulfide solid electrolyte with high ion mobility, characterized in that, The chemical formula of the solid electrolyte is Li θ Ge α P β Q ε S γ Te δ X 12-δ-γ ; Where Q is an element of Sb, As, Nb or V, and X is an element of Cl, Br or I; θ+4α+5(β+ε)-(γ+δ)-12=0, 9.5≤θ<10, 1<α≤2, 1<β≤2, 2.7≤α+β+ε≤3.2, 10.5<γ<12, 0<δ≤0.6; The solid electrolyte has an ionic conductivity of 12.48 mS·cm at 25-30℃. -1 The ionic conductivity at -50℃ is greater than or equal to 1 mS·cm. -1 .
2. A method for preparing a high-ion-mobility sulfide solid electrolyte as described in claim 1, characterized in that, include: According to the chemical formula of the solid electrolyte, Li2S powder, GeS2 powder, S powder, P powder, Te powder, LiX powder and Q2S5 powder are ground and mixed to obtain a mixed precursor. The mixture precursor is ball-milled to obtain mixture precursor powder; The mixed precursor powder is cold-pressed to obtain mixed precursor sheets; The mixed precursor sheet is transferred into a quartz tube, an inert gas is introduced into the quartz glass tube, and the quartz tube is necked, melted, and sealed. The quartz tube is heated to 250℃~350℃ at a rate of 2~10℃ / min, held at that temperature for 5~15h, and then placed in a quenching medium to cool for 10~30min to obtain a solid electrolyte.
3. The method for preparing a high-ion-mobility sulfide solid electrolyte according to claim 2, characterized in that, The process of ball milling the mixture precursor to obtain mixture precursor powder includes: The mixture precursor is placed in a ball mill jar, grinding beads are added, and the ball mill jar is placed in a ball mill and ball milled at a speed of 600~1200 rpm for 5~30 h to obtain the initial mixture precursor powder. The ball-to-material ratio in the ball mill jar is 2 to 1:1, and the particle size of the grinding balls is 2 to 8 mm. The initial mixture precursor powder is placed in a mortar and ground for 15-30 minutes to obtain the mixture precursor powder.
4. The method for preparing a high-ion-mobility sulfide solid electrolyte according to claim 2, characterized in that, During the cold pressing process, the pressure is 100~400MPa and the holding time is 2~10min.
5. The method for preparing a high-ion-mobility sulfide solid electrolyte according to claim 2, characterized in that, After cooling in a quenching medium for 10-30 minutes, the method further includes, Place the product inside the quartz tube in a mortar and grind it for 15-30 minutes.
6. The method for preparing a high-ion-mobility sulfide solid electrolyte according to claim 2, characterized in that, The inert gas is one or more combinations of argon, helium, and nitrogen.
7. The method for preparing a high-ion-mobility sulfide solid electrolyte according to claim 2, characterized in that, The quenching medium is liquid nitrogen, a mixture of ice and water, or a mixture of dry ice and ethanol.